2010
DOI: 10.1097/md.0b013e3181ca14ff
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-Associated Myositis and Anti-p155 Autoantibody in a Series of 85 Patients With Idiopathic Inflammatory Myopathy

Abstract: A new autoantibody against a 155-kDa protein has been described in patients with myositis. We conducted a study to determine the occurrence and types of cancer occurring in a cohort of patients with polymyositis (PM) or dermatomyositis (DM) and analyzed the value of this autoantibody as a serologic marker of cancer-associated myositis (CAM). Serum samples from all patients were examined by protein immunoprecipitation assays with HeLa cells to determine the presence of a 155-kDa protein band. HLA-DRB1 and DQA1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
72
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(81 citation statements)
references
References 24 publications
7
72
1
1
Order By: Relevance
“…However, one study reported that the performance of FDG-PET/CT for diagnosing cancer in patients with myositis (DM and PM) was comparable to that of broad conventional screening [39]. Also, antibodies to transcription intermediary factor-1c (antip155, anti-155/140, anti-p155/140) have been associated with cancer in adult patients with DM [41][42][43][44][45][46]. Nevertheless, the usefulness of these autoantibodies for cancer screening patients with myositis remains to be elucidated.…”
Section: Discussionmentioning
confidence: 96%
“…However, one study reported that the performance of FDG-PET/CT for diagnosing cancer in patients with myositis (DM and PM) was comparable to that of broad conventional screening [39]. Also, antibodies to transcription intermediary factor-1c (antip155, anti-155/140, anti-p155/140) have been associated with cancer in adult patients with DM [41][42][43][44][45][46]. Nevertheless, the usefulness of these autoantibodies for cancer screening patients with myositis remains to be elucidated.…”
Section: Discussionmentioning
confidence: 96%
“…In individuals with cancer, a mutation of p53 may lead to the development of cancer while the mutated p53 is recognized as non-self by the immune system and trigger autoantibodies to p53. Autoantibodies to p155/140 (transcription intermediary factor-1γ, TIF-1γ) have been described recently in strong association with cancer-associated DM [57][58][59][60]. Based on the tumor-suppressive effects of TIF-1γ described in murine models and human [61][62][63], it seems reasonable to hypothesize that TIF-1γ mutation is the primary event that leads to Fig.…”
Section: Mechanisms Of Myositis Autoantibody Production and Pathogenementioning
confidence: 96%
“…Over the last few years, it is now evident that cancer-associated DM is an antibody-rich rheumatic phenotype with the discovery of anti-TIF1 and more recently anti-NXP2 autoAb. Anti-TIF1 has now been described in around 15-25 % of DM cohort studies [57][58][59][60]. The identity of the 155/ 140 kDa protein was subsequently identified as the TIF1 (α, β, γ subunits) family proteins, with TIF1-γ the main target [60].…”
Section: Anti-tif1 and Anti-nxp2 Autoabmentioning
confidence: 99%